Photodynamic therapy-induced alterations in interstitial fluid pressure, volume and water content of an amelanotic melanoma in the hamster. - Leunig, M. (Nature Publishing Group, 1994)
The effect of photodynamic therapy (PDT) on interstitial fluid pressure (IFP), tumour volume and water content was measured in melanomas grown in hamsters. Unlike control tumours, treated tumours exhibited a 40-60% increase in volume at 1, 3 and 6 h post PDT. IFP also increased at 1 and 3 h after PDT, but decreased to 50% of control value after 24 h, presumably as a result of PDT-induced microcirculatory impairment.